Cancer-related cognitive impairment in racial and ethnic minority groups: a scoping review - Franco-Rocha, Oscar Y.; Lewis, Kimberly A.; Longoria, Kayla D.; De La Torre Schutz, Alexa; Wright, Michelle L.; Kesler, Shelli R. (Journal of cancer research and clinical oncology, 2023)
Purpose Disparities in cognitive function among racial and ethnic groups have been reported in non-cancer conditions, but cancer-related cognitive impairment (CRCI) in racial and ethnic minority groups is poorly understood. We aimed to synthesize and characterize the available literature about CRCI in racial and ethnic minority populations. Methods We conducted a scoping review in the PubMed, PsycInfo, and Cumulative Index to Nursing and Allied Health Literature databases. Articles were included if they were published in English or Spanish, reported cognitive functioning in adults diagnosed with cancer, and characterized the race or ethnicity of the participants. Literature reviews, commentaries, letters to the editor, and gray literature were excluded. Results Seventy-four articles met the inclusion criteria, but only 33.8% differentiated the CRCI findings by racial or ethnic subgroups. There were associations between cognitive outcomes and the participants’ race or ethnicity. Additionally, some studies found that Black and non-white individuals with cancer were more likely to experience CRCI than their white counterparts. Biological, sociocultural, and instrumentation factors were associated with CRCI differences between racial and ethnic groups. Conclusions Our findings indicate that racial and ethnic minoritized individuals  may be disparately affected by CRCI. Future research should use standardized guidelines for measuring and reporting the self-identified racial and ethnic composition of the sample; differentiate CRCI findings by racial and ethnic subgroups; consider the influence of structural racism in health outcomes; and develop strategies to promote the participation of members of racial and ethnic minority groups.